Western-centred civilization and reawakening parameters of Islamic Civilization for the new world order - Kayadibi, Saim (University of Malaya, 2011)
Muslim’s contribution to the development of world civilization is a significant matter which deserves a further investigation. The Muslim Empires all the way through their leadership role of Islamic world took momentous responsibilities and steps in shaping the construction of the Islamic civilization according to the changing times. Researching and studying the magnificent intellectual contributions of Muslims to the world civilization is a necessary requirement for an Islamic renaissance and revival movements which aim at rebuilding the Islamic civilization. Western civilization was being posed as the sole civilization which had given progress to the world, the contribution of other civilizations was being denied and ignored and, therefore, it was being imposed as a model to non-western world. Against this prevailing and dominating trend, new intellectuals came with an alternative concept of Islamic civilization and remained the loyal defenders of it until the day. It is an erroneous perception to compare history of civilizations with the life cycle of human beings: they are not alike, human beings are born, they grow and die; however, civilizations are born, they grow and retreat for later reawakening time; it is a treasure which rears when the humanity needs it for reformation and change. This paper attempts to underline the significance of Islamic civilization through exploring Muslims’ reawakening process and needs of humanity for a new world order which reflect the contribution of Islamic civilization in terms of ontological freedom, security and human rights. Keyword: Islamic Civilization; Freedom; Human Rights; Western-centred Civilization.